Analysis Absorption of Labor in the ASEAN Region - Hafiludin, Alan; Zuhroh, Idah; Aksari Anindyntha, Firdha (Jurnal Ilmu Ekonomi JIE, 2024)
This research aims to determine the impact of wages, investment, economic growth and internet users on labour absorption in all countries in the ASEAN region in 2014-2021. This research uses secondary data obtained from the World. The data analysis technique uses panel data regression analysis. Based on the findings of data analysis, the fixed effect model (FEM) is the model that best suits this research. The analysis results show that investment, economic growth, and internet users had a positive and significant effect on labour absorption in ASEAN in 2014-2021, while wages negatively and significantly impacted labour absorption in ASEAN in 2014-2021.